Determinación de los parámetros físicos para un prototipo de farola eólica de eje vertical orientado al alumbrado exterior, en el periodo 2021. - Santander Puli, Segundo Anibal (2021)
In this degree work, the physical parameters of a wind street light prototype were determined, which is used for the exterior lighting of a sports field, taking advantage of the natural resource of renewable energies in order to provide electric service to the habitants. Thus, a study and analysis of the wind power potential were carried out during a year, resulting, a wind power system was dimensioned to cover the demand required by the surface of the sports field. The physical parameters obtained in the area have allowed establishing a suitable design of a Savonius type wind turbine. It was taken advantage of all the natural resources that the area can provide and by sizing the electrical elements, a battery of 100 Ah/day to a 12 V system, a charge regulator of 50 A at 120 V, and a current inverter of 500 W was obtained, fulfilling the objective of an excellent lighting system and above all efficient and contributing to the environment with renewable energies. The wind turbine design was made in the SolidWorks premium 2021 software, considering one of the most relevant physical parameters such as wind direction and speed. Consequently, the appropriate design of the blades and the size of the wind turbine was made, to later perform a simulation with the Matlab Simulink software, and employing the wind potential that was obtained, it was possible to light a 120 W electric lamp. Through a technical-economic analysis, it can be stated that the prototype is feasible for its implementation.